Increased Expression of DNA Methyltransferase 1 and 3B Correlates with Tumor Grade in Laryngeal Squamous Cell Carcinoma - Nooshin Mohammadzadeh; Fatemeh Mosaffa; Ehsan Khadivi; Rosa Jahangiri; Khadijeh Jamialahmadi (Pharmaceutical Sciences, 2021)
Background: DNA methyltransferase (DNMT) enzymes, encoded by DNMT1, DNMT3A andDNMT3B genes, play a major role in the development of cancers through aberrant promotermethylation. Due to little information about the biological and clinical significance of expressionchanges of these genes in Laryngeal Squamous Cell carcinoma (LSCC), the current study wasdesigned to evaluate the contribution of DNMTs expression as potential diagnostic biomarkersin progression of LSCC. Methods: DNMT1, DNMT3A and DNMT3B expressions in tumoral and normal tissues fromthirty-three LSCC patients were evaluated by relative comparative real-time PCR, prior toany therapeutic intervention. Relationship between genes expression and clinicopathologicalfeatures were also analyzed. Results: The mRNA expression levels of all three DNMTs (DNMT1, DNMT3A and DNMT3B)were significantly elevated in LSCC tumor specimens compared to that of non-tumor tissues(P<0.0001, P=0.011 and P<0.0001, respectively). The expression of DNMT1 and DNMT3Bwas strongly associated with histopathological tumor grade. Moreover, the mRNA expressionlevels of DNMT3A were significantly correlated with laryngopharyngeal reflux. No significantrelationships existed with other clinicopathological parameters. Conclusion: Data showed that the expression levels of DNMT1, DNMT3A and DNMT3Bmarkedly increased in LSCC tissues. DNMT1 and DNMT3B were mainly overexpressed in highgrade LSCC tumors, therefore, they may have a role in LSCC progression. It seems that thesegenes may serve as diagnostic biomarkers in development of LSCC.